Designing Supplementary Speaking Materials Based On Communicative Language Teaching (CLT) - Mutiara Yulia Efendi (CV. Eureka Murakabi Abadi, 2022)
The research is aimed at designing supplementary speaking materials based on Communicative Language Teaching (CLT) and revealing the efficacy of developed supplementary speaking materials in improving speaking skill. This research belongs to research and development (R&D) and adopts the ten steps of Borg and Gall's model. (2016) which are simplified into six steps. They are (1) Research and information collecting, (2) Planning, (3) Developing Form Product, (4) Preliminary Field Testing, (5) Main Product Revision, (6) Final Product Revision. This research is started by determining needs and principles. The needs were carried out by doing document analysis, class observation, and interviews. The need analysis was needed to design the content and sequence to achieve the goals. CLT became a choice for format and presentation. For the second objective that is to reveal the efficacy of materials, assessment, and monitoring were carried out in the field-testing which the material was tried out. The findings show that (1) the design supplementary speaking materials based on CLT that were designed in this research fulfilled the criteria of the R&D model by Borg and Gall, course grid adopted the curriculum design by Nation and Macalister (2010) and followed Communicative Language Teaching (CLT) by Littlewood (1981) was chosen to be an approach in deciding the activities, and (2) the efficacy of the supplementary speaking materials help students to improve their speaking skill. As conclusion that these supplementary speaking materials are useful and attract students to be communicatively involved in the teaching and learning process